Vein Versus Prosthetic Graft for Femoropopliteal Bypass Above the Knee: A Systematic Review and Meta-Analysis of Randomized Controlled Trials. (August 2019) - Sharrock, Martin; Antoniou, Stavros A.; Antoniou, George A.
Conflicting evidence exists surrounding which conduit material is preferable in above-knee femoropopliteal bypass surgery. We performed a systemic review of electronic information sources to identify randomized controlled trials (RCTs) comparing vein versus prosthetic grafts in above-knee femoropopliteal bypasses. Eight RCTs reporting 1271 grafts (608 saphenous vein and 663 prosthetic) in 1132 patients were included. At 5 years, the vein group had significantly higher primary patency (odds ratio [OR]: 1.73, 95% confidence interval [CI]: 1.17-2.55, P = 0.006), primary assisted patency (OR: 4.02, 95% CI: 2.84-5.70, P < 0.0001), and secondary patency (OR: 1.83, 95% CI: 1.20-2.80, P = 0.005) rates compared with the prosthetic group. The vein group required significantly fewer reinterventions (OR: 0.33, 95% CI: 0.18-0.60, P = 0.0003). There was no significant difference in 30-day mortality (risk difference: −0.01, 95% CI: −0.02 to 0.01, P = 0.34), 30-day morbidity (OR: 1.58, 95% CI: 0.61-4.06, P = 0.35), major amputation (OR: 0.71, 95% CI: 0.43-1.18, P = 0.19), or overall survival (OR: 0.95, 95% CI: 0.70-1.30, P = 0.76) when comparing vein versus prosthetic grafts. Our analysis supports the use of the saphenous vein in above-knee femoropopliteal bypass grafting owing to its superiority in primary, primary assisted, and secondary patency rates and less need for reintervention when compared with prosthetic grafts.